In Vivo Changes of the Oxidation-Reduction State of NADP and of the ATP/ADP Cellular Ratio Linked to the Photosynthetic Activity in Chlamydomonas reinhardtii - Forti, Giorgio (The American Society for Plant Biologists, 2003)
The ATP/ADP and NADP/NADPH ratios have been measured in whole-cell extract of the green alga Chlamydomonas reinhardtii, to understand their availability for CO(2) assimilation by the Calvin cycle in vivo. Measurements were performed during the dark-light transition of both aerobic and anaerobic cells, under illumination with saturating or low light intensity. Two different patterns of behavior were observed: (a) In anaerobic cells, during the lag preceding O(2) evolution, ATP was synthesized without changes in the NADP/NADPH ratio, consistently with the operation of cyclic electron flow. (b) In aerobiosis, illumination increased the ATP/ADP ratio independently of the intensity used, whereas the amount of NADPH was decreased at limiting photon flux and regained the dark-adapted level under saturating photon flux. Moreover, under these conditions, the addition of low concentrations of uncouplers stimulated photosynthetic O(2) evolution. These observations suggest that the photosynthetic generation of reducing equivalents rather than the rate of ATP formation limits the photosynthetic assimilation of CO(2) in C. reinhardtii cells. This situation is peculiar to C. reinhardtii, because neither NADPH nor ATP limited this process in plant leaves, as shown by their increase upon illumination in barley (Hordeum vulgare) leaves, independent of light intensity. Experiments are presented and were designed to evaluate the contribution of different physiological processes that might increase the photosynthetic ATP/NADPH ratio—the Mehler reaction, respiratory ATP supply following the transfer of reducing equivalents via the malate/oxaloacetate shuttle, and cyclic electron flow around PSI—to this metabolic situation.